EL-MENHELU'S-SÂFÎ FÎ ŞERHİ'L-VÂFÎ ADLI ESERİ ÖZELİNDE ED-DEMÂMÎNÎNÎ'NİN DİL FELSEFESİ - KAYA, İRFAN (Fırat Üniveristesi, 2015)
Bir olgu olarak dil insanlar ve toplumlar gibi yaşayan, değişen ve zamanın geçmesiyle yavaş yavaş yok olabilen bir yapıdır. Yeryüzünde yaşamış ve yaşayagelen bütün diller bu şekilde yok olma tehlikesiyle karşı karşıyadır. Fakat Arapça Kur'ân-ı Kerim'in dili olması sayesinde diğer dillerin maruz kaldığı bu akıbetten korunabilmiştir. Müslümanların bu dilin kaide ve kelimelerini tespit edip koruma yönündeki yoğun gayretleri sonucunda yüzyıllardır genel hatlarıyla değişmeden kalabilmiştir. Biz çalışmamızda yukarıda zikredilen bu çabaların bir parçası olarak görülebilecek bir eser olan el-Menhelu's-sâfî fî şerhi'l-vâfî adlı kitabı ve bu eserin müellifi olan Bedruddîn ed-Demâmînî'yi hayatı, ilmi kişiliği ve nahiv ilmindeki yeri itibariyle ele aldık. Nahivle ilgili görüş ve tercihlerini, zikrettiğimiz eseri ışığında tahlil etmeye çalıştık. Anahtar Kelimeler: Nahiv, Kur?ân, Hadis, Demaminî, Arap ?iiri, Kıyas, Delil.

Language, as a phenomenon, is a structure that lives like people and communities, changes and may disappear gradually as time goes by. All languages which lived and are still living on Earth are faced to danger of extinction in this way. But, Arabic langua.g.e, thanks to its being the language of the Holy Quran, has been preserved from the fate that faced by other languages. It has remained unchanged in general for centuries as a result of Muslims' intensive efforts in order to determine and protect its rules and vocabulary. In our study, we examined the book, Al-Manhal Al-Safi Fi Sharh Al-Wafi, a work which can be seen as part of the above-mentioned efforts, and the author of this work, Bedreddin al-Demaminî, with respect to his life, scientific personality, and his place in the science of nahw (syntax). We tried to analyze his opinions and pref'erences regarding nahw under the light of his abovementioned work. Keywords: Nahw, Quran, Hadith, Demaminî, Arabic poetry, Comparison, Evidenc
Al-Demaminî's philosophy of langua.g.e in specific to his work, al-Manhal Al-Safi Fi Sharh Al-Wafi
Keywords: Dilbilim; Doğu Dilleri ve Edebiyatı